Antioxidant effect and oral acute toxicity of thermal waters from San Antonio de Putina-Puno - Llahuilla, José A. (2014)
Were studied the antioxidant effect and toxicity of the hot springs of San Antonio de Putina-Puno. Were used methods of lipid antiperoxidation, malondialdehyde (expressed as TBARS), in vivo oral acute toxicity at fixed dose according to 423 OECD and the physical chemistry composition by inductively coupled plasma source mass spectrometry (ICP-MS). The antioxidant effect presented significant difference between control group (0,0527 ŋm) and the study group (0,0390 ŋm) and malondialdehyde (p<0,05) and in vivo oral acute toxicity at fixed-dose treatment. Not evident signs of intoxication, moreover, in the composition of these hot springs were found: chloride 71,9%, sodium 80,3 % and sulphate 22,7% meq. Was concluded that the thermal mineral hot springs, are not toxic, have antioxidant effect and are chlorinated, sulphate and sodium type.